(untitled) (Journal of the College of Basic Education, 2022)
The aim of the research is to prepare electrically insulating materials with irregular shapes by slip casting method and to study the electrical and physical properties. The strength of the electrical insulation, the research mixtures (kaolin - glass) were prepared in different weight ratios, which are (20, 40, 60, 80%), and the best percentage was (60) glass.